2021
DOI: 10.3390/life11101095
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Natural Compounds with Antiplatelet and Anticoagulant Activity and Their Potential Role in the Treatment of Thrombotic Disorders

Abstract: Natural anticoagulant drugs can be obtained from plants, rich in secondary bioactive metabolites which, in addition to being effective antioxidants, also possess anticoagulant and antiplatelet properties and, for this reason, can be excellent candidates for the treatment of thrombotic diseases. This review reports an overview of the hemostatic process and thrombotic disorders together with data on plants, more and less common from around the world, containing bioactive compounds characterized by antiplatelet a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 175 publications
(176 reference statements)
0
11
0
Order By: Relevance
“…The aqueous extract exhibited a higher clotting time in comparison to the standard warfarin. It has been reported that organosulfur compounds and phenolic contents of garlic extract are responsible for its high anticoagulant effect (56). The one-tailed t-test was performed to statistically analyze the negative control and test sample data to assess the significance level of garlic extract for each concentration of all in vitro assays.…”
Section: Discussionmentioning
confidence: 99%
“…The aqueous extract exhibited a higher clotting time in comparison to the standard warfarin. It has been reported that organosulfur compounds and phenolic contents of garlic extract are responsible for its high anticoagulant effect (56). The one-tailed t-test was performed to statistically analyze the negative control and test sample data to assess the significance level of garlic extract for each concentration of all in vitro assays.…”
Section: Discussionmentioning
confidence: 99%
“…Many plants and their bioactive compounds having antioxidant and anti-inflammatory potential also exhibit anticoagulant effects [27]. Various parts of C. decidua are also reported to be rich in many phyto-constituents such as flavanoids, alkaloids, phenols, terpenoids, carbohydrates, protein, crude fiber and minerals such as Na, Ca, P, Fe, Zn, Cu, Mg, and compounds like capparine, cappariline, capparisine, capparisinine, capparidisine, cadabicine, stachydrine, codonocarpine, isocodonocarpine etc.…”
Section: Discussionmentioning
confidence: 99%
“…Chamomilla is a popular herbaceous plant native to Europe and Western Asia, and the plant is known for its potent medicinal effects. The main phytochemicals of the chamomilla include phenolic compounds (especially flavonoids quercetin, apigenin, or luteolin, among others) [ 125 ]. Chamomilla demonstrates potent effects on platelet inhibition.…”
Section: Phytochemicals With Protective Effects Against Thrombosismentioning
confidence: 99%